Analysis the Quality of Human Resources and the Effectiveness of Higher Education Management on Student Academic Performance at Universities in Samarinda, East Kalimantan - Dina Destari (The Eastasouth Journal of Learning and Educations, 2023)
This study's primary focus is on how much a college in Samarinda, East Kalimantan, impacts students' academic achievement in relation to the calibre of its human resources and the efficiency of its administration. This quantitative study explores the impact of human resource quality and college management effectiveness on student academic performance in universities located in Samarinda, East Kalimantan, Indonesia. The research sample included 100 participants representing students, academic staff, and administrative personnel. Data were collected through surveys and academic records, and the analysis was conducted using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) path modeling. The results indicate that both "Higher Education Management" and "Quality of Human Resources" significantly predict "Student Academic Performance." Participants across stakeholder groups generally held positive perceptions of higher education management and human resource quality. The findings underscore the importance of effective management and quality human resources in enhancing student academic outcomes. This research contributes valuable insights for higher education institutions in Samarinda and policymakers aiming to improve the quality of higher education management and resource allocation. It also suggests potential directions for future research in the field.